In Vivo Disintegration and Bioresorption of a Nacre-Inspired Graphene-Silk Film Caused by the Foreign-Body Reaction - Linhao Li; Yanbing Liang; Guohang Wang; Peng Xu; Lingbing Yang; Sen Hou; Jin Zhou; Lizhen Wang; Xiaoming Li; Li Yang; Yubo Fan (iScience, 2020)
Summary: Graphene-based substrates are emerging as a promising functional platform for biomedical applications. Although dispersible graphene sheets have been demonstrated to be biodegradable, their assembled macroscopic architectures are biopersistent because of strong π-π interactions. In this study, we developed a nacre-inspired graphene-silk nanocomposite film by vacuum filtration with a subsequent green chemical reduction procedure. The “brick-and-mortar” architecture not only ensures the mechanical and electrical properties of the film but also endows it with disintegrable and bioresorbable properties following rat subcutaneous implantation. Furthermore, covalent cross-linking leads to the formation of graphene with decreased interlayer spacing, which effectively prolongs the residence time in vivo. We found that enzymatic treatment created microcracks on the film surface and that the foreign-body reaction was involved in the deformation, delamination, disintegration, and phagocytosis processes of the nanocomposite films. This bioinspired strategy paves the way for the development of high-performance graphene-based macroscopic biomaterials with tunable bioresorbability.